Strategi Pengelolaan Dana Alokasi Khusus Bidang Kelautan Dan Perikanan Di Kabupaten Kepulauan Anambas - Lenny Romauli Marpaung; Hermanto Siregar; Tanti Novianti (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2024)
ABSTRACT The Anambas Islands is one of the regions in the Riau Islands province with a vast proportion of sea, accounting for 98.74 percent of its total area. Through the mechanism of decentralization, most of the functions of marine and fisheries gradually become part of the affairs of the district/city. The transfer of authority is accompanied by the transfer of financing through a balance fund, so that with the increasing funds managed by the region, it is expected that the development of marine and fisheries will improve. DAK is one of the fiscal instruments of the balance fund, which plays an important role in achieving national priority areas (DJPK 2016). As noted by BAPPENAS (2013) in the national development priorities 2015-2019, the main issues and challenges in the development of marine and fisheries are suboptimal production infrastructure, namely in the capture fleet, ports, agricultural roads, land, and access to business development (capital and markets). The aim of this research is to formulate strategies for managing the Special Allocation Fund (DAK) in the marine and fisheries sector from 2011 to 2016 in the Anambas Islands Regency using the Analytical Hierarchy Process (AHP) method. Based on the AHP method, the priority strategies include the evaluation of regulations related to DAK management, the placement of support personnel, socialization and law enforcement, improving coordination systems, and forming Joint Business Groups. Keywords: Analysis Hierarchy Process, Special Allocation Fund, Marine, Fisheries, Strategy